Studies on a die-back of Arabica coffee in South India; role of pests and parasites - D'Souza, G.I. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The pattern of field incidence and associations indicated that the die-back of arabica was not caused by insect pests or other microparasites. The die-back was a hot-weather die-back and not a cold weather die-back. Coffee plants grown under exposed conditions were invariably subject to the malady. The die-back could be arrested by provision of adequate over-head shade.